2018
DOI: 10.1175/jpo-d-18-0003.1
|View full text |Cite
|
Sign up to set email alerts
|

Observed Atlantification of the Barents Sea Causes the Polar Front to Limit the Expansion of Winter Sea Ice

Abstract: Barents Sea Water (BSW) is formed from Atlantic Water that is cooled through atmospheric heat loss and freshened through seasonal sea ice melt. In the eastern Barents Sea, the BSW and fresher, colder Arctic Water meet at the surface along the Polar Front (PF). Despite its importance in setting the northern limit of BSW ventilation, the PF has been poorly documented, mostly eluding detection by observational surveys that avoid seasonal sea ice. In this study, satellite sea surface temperature (SST) observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
172
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 78 publications
8
172
0
Order By: Relevance
“…The latter has been suggested to be the most important in the Barents Sea, and this is why the influence of AW is mainly a winter signal (Onarheim et al, ). Another recent study by Barton et al () showed that since 2005, the winter sea ice edge in the Barents Sea has been restrained by an increase in temperature gradient across the Polar Front, which is a potential vorticity constrained shelf slope current in the eastern Barents Sea. This change may be driven by an increase in AW temperature (Barton et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter has been suggested to be the most important in the Barents Sea, and this is why the influence of AW is mainly a winter signal (Onarheim et al, ). Another recent study by Barton et al () showed that since 2005, the winter sea ice edge in the Barents Sea has been restrained by an increase in temperature gradient across the Polar Front, which is a potential vorticity constrained shelf slope current in the eastern Barents Sea. This change may be driven by an increase in AW temperature (Barton et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Atmospheric forcing may be the biggest contributor to the sea ice loss (Serreze et al, 2007), but ocean heat storage and transport play an important role in certain regions (Carmack et al, 2015;Perovich & Richter-Menge, 2015;Polyakov et al, 2017). For example, the decline and variability in winter sea ice cover north of Svalbard and in the Barents and Kara Seas is linked to an increased and warmer inflow of Atlantic Water (AW; Årthun et al, 2012Barton et al, 2018;Li et al, 2017;Onarheim et al, 2014Onarheim et al, , 2015Onarheim et al, , 2018. The Barents Sea experiences the fastest surface warming in the Arctic (Screen & Simmonds, 2010), and a recent study by Lind et al (2018) found that the northern Barents Sea has transitioned from a cold Arctic to a warm Atlantic-dominated regime.…”
Section: Introductionmentioning
confidence: 99%
“…Climate model ensemble means (under continued increasing emissions) show a sustained incursion of Atlantic Water (marked by contours of the 1 ° C isotherm at 200‐m depth in Figure 12 of Årthun et al, ), from its present location in the vicinity of Fram Strait and the Barents Sea (see, e.g., Barton et al, ) to almost paralleling the Lomonosov Ridge in the 2070s such that warm Atlantic Water fills the entire Eurasian Basin (Årthun et al, ). The main effect of this is a decrease in winter sea‐ice thickness, by around 1.2 m between the 2010s and 2070s; average ocean‐to‐ice heat fluxes increase from around 0.5 to 5 W m −2 in the Eurasian Basin between these two periods.…”
Section: Arctic Ocean Variability Climate Change and Future Perspecmentioning
confidence: 99%
“…While IOPs and AOPs in surface waters of the Arctic Ocean have gotten more attention recently (e.g., Granskog et al, ; Hill, ; Lund‐Hansen et al, ; Matsuoka et al, ; Pavlov et al, , ; Pegau, ), there are fewer relevant studies in the Atlantic inflow region in the European sector of the Arctic Ocean. Recent publications report dramatic effects of the northward and eastward expansion of warm Atlantic Water (AW) into the Central Arctic Ocean and in the Barents and Kara Seas on sea ice distribution and melt (Barton et al, ; Lind et al, ; Polyakov et al, ). This, in turn, justifies the need for a more detailed overview of bio‐optical properties in surface waters of Atlantic origin, their seasonality, and interannual variability, as well as insights into how these bio‐optical properties change once AW interacts with sea ice, Polar Surface Water (PSW) and regional water masses influenced by terrestrial discharge and glacial melt.…”
Section: Introductionmentioning
confidence: 99%